EFFECTIVENESS OF ELECTROMYOGRAPHY BIOFEEDBACK IN COMMON KNEE DISORDERS-A REVIEW - NARESH BHASKAR RAJ,; DR. AMRAN BIN SHOKRI,; DR. HAIRUL ANUAR HASHIM,; DR. SRILEKHA SAHA,; DR. MOHD BIN SAAT ISMAIL,; CHOO MORLEY LIZA,; DR. SOUMENDRA SAHA, (International Journal of Pharma and Bio Sciences, 2015)
Present study focuses on examining effectiveness of Electromyography (EMG) biofeedback in treatment of ailments and disorders related to knee-joint. In order to carry out the literature survey, terms knee and biofeedback were used as keywords in the databases such as, Physiotherapy evidence Database (PEDro), Cumulative Index of Nursing and allied Health literature (CINAHL), Sport DISCUS and PubMed. Outcomes from the researches conducted incorporating EMG biofeedback and quadriceps exercises used for knee rehabilitation were analysed. Data from the randomised controlled trials were collected on various categories such as, the number of patients; age-range, sex of the participants, type of injury/disorder, duration of symptom, placement of electrodes etc were considered under the purview of the review. Out of two-hundred twenty articles, after all scrutiny done based on the PRISMA guidelines, only eleven met the criteria for inclusion and were taken up for analysis. While eight of the selected articles were analysed for functional outcomes and seven others were analysed for quadriceps strength. A total of 413 participants was included in the trials mentioned. Age of the participants ranged from as low as 23 till 55 ± 7.09. The average PEDro score of the trials included in the review was 5.619. EMG biofeedback (BF) intervention technique has been observed as beneficial for the post-surgical knee disorders rather than chronic disorders like Osteoarthritis.